Universal prevention for non-suicidal self-injury in adolescents is scarce - A systematic review - Bürger, Arne; von Schoenfeld, Cornelia; Scheiner, Christin; Seidel, Alexandra; Wasserscheid, Antonia; Gad, Doreya; Kittel-Schneider, Sarah; Romanos, Marcel; Reiter, Andrea M. F. (Frontiers in Psychiatry, 2023)
Non-suicidal self-injury (NSSI) during adolescence is a high-risk marker for the development and persistence of mental health problems and has been recognized as a significant public health problem. Whereas targeted prevention was indeed shown to be effective in reducing NSSI and improve mental health problems, access to such programs is limited. By face validity, universal prevention of NSSI seems an ideal starting point for a stepped-care model to circumvent a lack of resources in the medical care system. However, it is yet unclear how effective such approaches are. Here, we provide a summary of existing work on universal prevention of NSSI in adolescents younger than 21 years based on a systematic literature search. We found that only seven studies are available. None of the programs evaluated was found to be effective in reducing the incidence or frequency of NSSI. After providing a comprehensive summary of the existing work, we evaluate the fact that existing work primarily focusses on selected/targeted prevention and on psychoeducational methods. We are developing implications for future directions in the field of universal prevention of NSSI.